Pericancerous lymph node imaging with indocyanine green‐guided near‐infrared fluorescence in radical esophagectomy: Protocol for a single‐center, prospective, randomized controlled clinical trial. Issue 15 (29th June 2022) - Du, Jianting; Xu, Guobing; Yang, Zhang; Zheng, Bin; Chen, Chun
Abstract: Introduction: The incidence and mortality rates of esophageal carcinoma are higher than those of most malignancies in humans. Radical esophagectomy is the preferred treatment for early‐stage esophageal cancer. However, the extent of lymphadenectomy during radical esophagectomy remains controversial. Indocyanine green (ICG) is the most commonly used imaging agent for the diagnosis of tumors and metastatic lymph nodes in clinical settings. Thus, the main aim of this study was to evaluate pericancerous lymph nodes imaging in video‐assisted thoracoscopic surgery radical esophagectomy using a near‐infrared (NIR) ICG imaging system and to improve the detection rate of sentinel lymph nodes (SLNs) and overall survival of patients with esophageal cancer. Methods: This was a single‐center, prospective, randomized controlled clinical trial (allocation rate = 1:1). Forty treatment‐naive esophageal cancer patients were recruited and divided into two groups: the ICG and control groups. The inclusion criteria were age, absence of preoperative neoadjuvant therapy, elective surgery, and signed informed consent. Data of participants at four different time points (preoperation, intraoperation, postoperative 1 week and 3 months) were collected and recorded. The main endpoint of this study was to explore the accuracy and false‐negative rate of lymphadenectomy using NIR‐ICG fluorescence imaging and to identify the location of esophageal cancer SLN combined with postoperative pathological reports. Discussion: This trial will provide more evidence on the extent of lymph node dissection for esophageal cancer and contribute to the development of treatment guidelines for esophageal cancer. Trial registration number: NCT04615806. Abstract : A figure of the study design is shown. In our study, we aimed to evaluate pericancerous lymph nodes imaging in video‐assisted thoracoscopic surgery(VATs) radical esophagectomy using a near‐infrared(NIR) ICG imaging system and to improve the detection rate of sentinel lymph nodes(SLN) and overall survival of patients with esophageal cancer. This trial will provide more evidence on the extent of lymph node dissection for esophageal cancer and contribute to the development of treatment guidelines for esophageal cancer.